Gender and Institutional Differences in Job Satisfaction, Professional Stress & Work Family Conflict in Academia - Shehla A. Yasin, Sana Naqvi (Pakistan Journal of Psychology, 2016)
A comparative exploratory approach was adopted in this study to explore gender and institutional (i.e. public and private sector) differences regarding job satisfaction, professional stress, and work family conflict in school, college and university teachers in Lahore. The participants (N= 240) were selected with an equal number of men (n=120) and women (n=120) from all three academic segments i.e. schools (n =80), colleges (n =80) and universities (n =80). Each segment was further subdivided into equal number of public and private institutes. The measures used in the study were: Job in General Scale (Ironson, Smith, Brannick, Gibson, & Paul, 1989), Professional Life Stress Scale (Fontana, 1989), Work-Family Conflict Scale (Kopleman, Greenhaus, & Connolly, 1983). The t-test was employed to examine the differences. The results indicated female teachers scored significantly higher on work-family conflict than male teachers. Further, teachers of public sector scored higher on work-family conflict than teachers of private sector. Thus, it can be concluded that gender and academic institute has significant effect on work family conflict.